Epidemiology and structure of congenital anomalies of the newborns in the region of Novi Sad (Vojvodina, Serbia) in 1996 and 2006 - Ristivojević, Anđelka; Lukić Đokić, Petra; Katanić, Dragan; Dobanovački, Dušanka; Jovanović Privrodski, Jadranka (Vojnosanitetski pregled, 2017)
Background/Aim. According to the World Health Organization (WHO) definition, congenital anomalies are all disorders of the organs or tissues, regardless of whether they are visible at birth or manifest in life, and are registered in the International Classification of Diseases. The aim of this study was to compare the incidence and structure of prenatally detected and clinically manifested congenital anomalies in the newborns in the region of Novi Sad (Province of Vojvodina, Serbia) in the two distant years (1996 and 2006). Methods. This retrospective cohort study included all the children born at the Clinic for Gynecology and Obstetrics (Clinical Center of Vojvodina) in Novi Sad during 1996 and 2006. The incidence and the structure of congenital anomalies were analyzed. Results. During 1996 there were 6,099 births and major congenital anomalies were found in 215 infants, representing 3.5%. In 2006 there were 6,628 births and major congenital anomalies were noted in 201 newborns, which is 3%. During 1996 there were more children with anomalies of musculoskeletal system, urogenital tract, with anomalies of the central nervous system and chromosomal abnormalities. During the year 2006 there were more children with cardiovascular anomalies, followed by urogenital anomalies, with significant decline in musculoskeletal anomalies. The distribution of the newborns with major congenital anomalies, regarding perinatal outcome, showed the difference between the studied years. In 2006 the increasing number of children required further investigation and treatment. Conclusions. There is no national registry of congenital anomalies in Serbia so the aim of this study was to enlight this topic. In the span of ten years, covering the period of the NATO campaign in Novi Sad and Serbia, the frequency of major congenital anomalies in the newborns was not increased. The most frequent anomalies observed during both years implied the musculosketelal, cardiovascular, urogenital and central nervous system. In the year 2006 there was a significant eruption of cardiovascular anomalies and a significant decrease of musculoskeletal anomalies, chromosomal abnormalities and central nervous system anomalies, while the number of urogenital anomalies declined compared to the year 1996.